EDUKASI SAY NO TO OBESITY (SOTO) DENGAN POLA HIDUP SEHAT DI KARANG TARUNA DEPOK JAYA - Aminah, Hafizha; Fauzi, Karina Fanny; Muslih, Farhani; Jevon, Ariel Bintang; Osya, Talitha Salma; Humaira, Anggita; Khadijah, Najwa; Azizah, Hanna Restiana; Azalia, Maritza; Eriany, Khalisa Puti Dwi; Hardiyanto, Lutfi (Universitas Sanata Dharma, 2025)
In this modern era of instant gratification, the problem of obesity is increasing, and adolescents are the most vulnerable age group to health problems. This study aims to increase the knowledge of Karang Taruna (Youth Organization) Depok Jaya about obesity and encourage them to adopt a healthy lifestyle through the ‘Say No to Obesity’ (SOTO) campaign. This quantitative study uses non-parametric statistical tests in the form of the Wilcoxon Test. The respondents in this study were 30 people who were part of the Youth Organization of Depok Jaya Village, Pancoran Mas District, Depok City. The results showed that 16 out of 30 respondents experienced an increase in knowledge. Statistical analysis comparing the results of the pretest and post-test shows a P-Value of 0.001 or 0.05, so that there is a difference in pretest and post-test scores or the effect of providing education on respondents' knowledge related to the knowledge that has been given through active learning methods. Feedback shows that games and activities could have a positive impact on respondents’ knowledge, which could be applied to future research.